Observations on the Proterozoic Seton Formation, East Arm of Great Slave Lake, Northwest Territories - Olade, M. A. D.; Morton, R. D. (Canadian Journal of Earth Sciences, 1972)
The Proterozoic (Aphebian) Seton Formation is shown to extend across almost the entire length of the East Arm structural subprovince of the Great Slave Lake region, Northwest Territories. Earlier described as greenstones or basalts and recently as an andesite–rhyolite suite, the volcanic rocks which characterize the Seton Formation are clearly of spilitic–keratophyric affinity. The formation is composed of a sequence of marine to subaerial, spilitic basalt flows, trachytic flows, quartz keratophyric–and spilitic–basic pyroclastics, volcanic sandstones, jasper, banded ironstones, and intercalated marine epiclastic sedimentary rocks. Small hypabyssal intrusions of albite granophyre, albite, and quartz porphyry represent minor subvolcanic phases. Petrographic descriptions of the lavas and pyroclastic rocks from Toopon Lake, the Fort Reliance area, and Seton Island are augmented by partial chemical analyses of 15 lavas from the latter locality. The volcanic–sedimentary Seton Formation, 1300 m thick in the SW of the East Arm, and 40 m thick in the Fort Reliance district, should be classified as a member of the Sosan Group, being in part laterally equivalent to the Akaitcho River Formation and the upper Kluziai Formation. The Aphebian Coronation Geosyncline during Seton times was thus characterized by effusive (partially submarine) island volcanism in the SW of the region, contemporaneous with shallow marine sedimentation towards the northeast part of the basin.